Analysis of TGFBI Gene Mutations in Three Chinese Families with Corneal Dystrophy. (22nd January 2019) - Zhao, Feng; Liu, Yuan; Guan, Tao
Abstract : Objective . To identify the types of TGFBI (transforming growth factor, beta-induced) gene mutations in three Chinese families with Reis–Bücklers corneal dystrophy (RBCD), lattice corneal dystrophy type I (LCDI), or Avellino corneal dystrophy (ACD) and to investigate the relationship between the phenotypes and genotypes of corneal dystrophy. Methods . Peripheral blood was collected from 24 patients and 76 phenotypically normal members in three Chinese families as well as from 100 healthy controls. Genomic DNA was extracted. All 17 exons of the TGFBI gene, and the exon-intron junctions were examined by polymerase chain reaction (PCR) and direct DNA sequencing to identify and analyse gene mutations. In addition, all members of the three families were subjected to detailed clinical examinations. Results . The heterozygous c.371G > T (p.R124L) mutation was detected in exon 4 of the TGFBI gene in nine patients from the family with RBCD. In contrast, this mutation was not found in the phenotypically normal members of the family. The heterozygous c.370C > T (p.R124C) mutation was found in exon 4 of the TGFBI gene in 11 patients from the family with LCDI. This mutation was not found in the phenotypically normal members of the family. The heterozygous c.371G > A (p.R124H) mutation was detected in exon 4 of the TGFBI gene in four patients from the family with ACD. Again, this mutation was not found in the phenotypically normal members of the family. The TGFBI gene mutations cosegregated with the disease phenotypes in the three families and exhibited an autosomal dominant mode of inheritance. No TGFBI gene mutations were detected in the 100 healthy controls. Conclusion . There is a high degree of correlation between the phenotypes and genotypes of TGFBI -linked corneal dystrophies. R124 represents a mutational hotspot in the TGFBI gene. Gene mutation analysis provides a reliable basis for the definitive diagnosis of corneal dystrophy.